Analisis Produk iB Tabung Haji Bank Jateng KCPS Tegal - Indah Wulandari Wilujeng; Pratomo Cahyo Kurniawan (Velocity: Journal of Sharia Finance and Banking, 2022)
Hajj is an obligatory worship for Muslims who are able to perform it. In connection with this study, I want to answer the formulation of the problem as follows: 1) How is the mechanism of the Hajj tube iB product at Bank Jateng Syariah Pembatu Tegal Branch, and 2) How is the application of the contract to the Hajj tube iB at Bank Jateng Syariah Tegal Sub-Branch. In writing this PPL assignment, the author uses field research methods by taking the research location at Bank Jateng Syariah KCPS Tegal using a qualitative descriptive approach. The data in this study consisted of primary data and secondary data, which were obtained through observation, interviews, and documentation. The results showed that a procedure or mechanism for the Hajj savings product at Bank Jateng KCPS Tegal, among others: opening an iB Tabung Haji account, registering for hajj initial deposit for hajj savings, provisions for getting a portion of hajj departures, paying off BPIH, as well as the benefits off the Hajj tube iB Procedure. In its application, the Hajj savings contract at Bank Jateng KCPS Tegal uses a wadiah yad dhamanah contract.